1992
DOI: 10.1007/bf02255289
|View full text |Cite
|
Sign up to set email alerts
|

Deformities in chironomid larvae as indicators of pollution (pesticide) stress

Abstract: Chironomid larvae ( Chironomus spp., Oicrotendipes conjunctus and Procladius paludicola) collected from Cox Creek and Aldgate Creek, South Australia, showed morphological abnormalities similar to those reported in other studies elsewhere in the world. The sediment of Cox Creek contained high concentrations of pesticides and there was a significant correlation between the occurrence of mouthpart and antennal deformities in larvae and the concentration of DDT and the herbicide, Dacthal| Laboratory experiments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 11 publications
(12 reference statements)
0
29
0
1
Order By: Relevance
“…Grour (2006) reported accumulated that concentrations of lead and copper in different host plants correlated with deviations from bilateral symmetry of cabbage aphids in terrestrial insects. In a related study, Warwick (1985) and Madden et al (1992) reported the effect of heavy metals on larval antennae development in Chironomus spp. Additionally, Bhattacharyay et al (2005) reported a high percentage of antennal deformities in Chironomus circumdatus under sediment Zn and Cu concentrations of 165.79 and 51.33 ppm, respectively, in an Indian polluted river.…”
Section: The Influence Of Water Quality and Environmental Parameters mentioning
confidence: 98%
“…Grour (2006) reported accumulated that concentrations of lead and copper in different host plants correlated with deviations from bilateral symmetry of cabbage aphids in terrestrial insects. In a related study, Warwick (1985) and Madden et al (1992) reported the effect of heavy metals on larval antennae development in Chironomus spp. Additionally, Bhattacharyay et al (2005) reported a high percentage of antennal deformities in Chironomus circumdatus under sediment Zn and Cu concentrations of 165.79 and 51.33 ppm, respectively, in an Indian polluted river.…”
Section: The Influence Of Water Quality and Environmental Parameters mentioning
confidence: 98%
“…It appears that different deformities may be caused by specific chemicals (Warwick and Tisdale 1988) or combination of different chemicals (Veroli et al 2010). Madden et al (1992) found increasing frequencies of deformities as levels of metal, coal tar, urban or agricultural runoff, and pesticides elevated. It is also known that heavy metal contamination is a major cause of deformities in the chironomid larvae (Martinez et al 2004;Bhattacharyay et al 2005;Al-Shami et al 2010a).…”
Section: Discussionmentioning
confidence: 97%
“…As the frequency of deformities and chromosome anomalies in G. glaucus larvae is generally high, it was hypothesised that contaminants in the water bodies were responsible . Laboratory experiments show that some pesticides cause deformities (Madden et al, 1992) . Kohn & Frank (1980) and Warwick (1990) suggest that heavy metals could also cause deformities in Chironomidae .…”
Section: Discussionmentioning
confidence: 99%